Knowledge, Attitude And Practices (Kaps) Related To Working At Height Among Construction Workers - Nurul Ain Maryam, Musa (2025)
This study analyzes about Knowledge, attitude and practices (KAP) related working at height (WAH) among construction workers. It highlights how crucial occupational safety and health (OSH) is for workers. It addresses the high-risk nature of the construction sector where numerous accidents occur due to inadequate safety measures, non-compliance and lack of proper training. This cross-sectional study involved 52 workers that were randomly selected to participate to evaluate their KAP levels. The study assessed the relationship between KAP value and socio-demographic variables including education levels and work experiences. Findings reveal that there was no significant correlation between KAP and variables despite most of respondents had high levels of KAP levels. Nonetheless, attitudes were greatly impacted by knowledge. It indicated the importance of hazard awareness, proper equipment usage and compliance with safety protocols. The study recommends safety training programs should be modified to meet the needs of companies and work tasks. Furthermore, enforcing safety measures and fostering safety culture through continuous learning and compliance. The findings are intended to reduce workplace incidents in the construction industry and better understanding of workers’ safety.